IMMATURE PLATELET FRACTION (IPF) DAN TROMBOPOIETIN DI SIROSIS HATI - Esti Rohani; Yetti Hernaningsih; Suprapto Ma’at; Ummi Maimunah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Liver cirrhosis remains a major clinical problem worldwide when associated with significant morbidity and mortality due toits complications. The presence of liver cirrhosis state affects the production of TPO influencing the process of thrombopoiesis. Thethrombopoiesis activity can be described by the Immature Platelet Fraction (IPF) value which is young platelets. The immature Plateletfraction value increases when platelet production enhances as well, on the contrary when the production declines, the IPF value is alsodecreased. This study was performed by cross-sectional method using 31 subject samples suffering from liver cirrhosis, consisting of ChildPugh score class A 2 samples (6.4%), Child Pugh score class B 9 samples (29%) and Child Pugh score class C 20 samples (64.6%). Theexamination of TPO levels was done by ELISA method using Humans TPO QuantikineR, the IPF value was examined using Sysmex XE-2100 Hematology Analyzer. The thrombopoietin serum levels in the samples ranged from 23.5 to 96.6 pg/mL with a mean of 45.1pg/mL.The immature Platelet Fraction values varied from 1.7% to 19.1% with a mean of 6.7%. From the statistical analysis, the levels of TPO andIPF at various degrees of the disease severity were not significantly different. There was no significant correlation between the TPO leveland IPF value, r = 0.038, p = 0.837. There was no significant difference between the TPO level and the IPF value in the splenomegaly andnonsplenomegaly state. In conclusion, based on this study no significant correlation was found between the IPF value with thrombopoietinserum levels, as well as the IPF and thrombopoietin levels, and there was no association with the disease severity.